Criminal Liability for Crimes Committed Using Cryptocurrencies - Al-Alili, Ameer Majeed Dahdouh; Abdullah, Zaid Salam (International Journal of Law and Public Policy (IJLAPP), 2026)
This research aims to clarify the actual works of criminal liability for crimes committed using cryptocurrency and to highlight the flaws of Iraqi legislation about this modern type of crime. Accordingly, an attempt has been made to analyse the elements, kinds, and difficulties of evidence, leading up to determining the legal system in which to protect from and suppress this type of crime, of which cyberspace is a part. This research is descriptive-analytical in nature, where legislation has been examined. The research indicates that the wide scope of risks involving cryptocurrency crimes makes it difficult to subject them to existing laws on movable property, especially since the legislator has omitted the criminalization of certain attacks like wallet hacking, while the sophisticated nature of making inquiries and collecting evidence complicates establishing a definitive link between the perpetrator and the transaction. All in all, this study finishes off with the need to develop or amend legislation to extend the definition of digital assets and criminalise attacks against them, strengthen investigative capacity in electronic tracking, establish units for cryptocurrency crimes, and regulate digital seizures and confiscation mechanisms. This further highlights the importance of modernising legislation in light of the criminal threat’s cryptocurrencies pose to upholding economic and legal security.